Environmental Education: Mario Boza’s Priority Work Interest. Some Pioneering Training Experiences (Biocenosis, 2022)
Since the beginning of the 70s, when various international events that highlighted the importance of education to achieve environmental improvement and natural resource conservation were organized, Costa Rica has created institutions that offer the opportunity to provide training in Environmental Education to various sectors of the population. Mario Boza played a very important role in making this possible as the founder of the School of Environmental Sciences at UNA, the Environmental Education Program at UNED, and the Environmental Education Program at MINAE. Various training courses were developed in these institutions with a clear vision of the multiplier effect that the target populations would have in raising awareness of the importance of resource conservation and sustainable management and searching for solutions to the environmental problems of their communities. This article presents some training experiences that were pioneering in the 70s and had a great impact in the country in the following two decades. It also notes the different target populations and the different modalities used.
Keywords: environmental education; natural resources; conservation; environmental issues; training; national parks